Mapping Knowledge Domains of Integration in BIM-Based Construction Networks: A Systematic Mixed-Method Review - Bin Guo; Tao Feng (Advances in Civil Engineering)
Building information modeling-based construction networks (BbCNs) are teams from several professional organizations working together to assume building information modeling- (BIM-) related assignments on BIM-enabled projects. With a view to achieving a better understanding of the knowledge domains on integration in BbCNs, a systematic mixed-method review of the relevant studies published from 2008 to 2018 is conducted in this study. An “integration pentagon” made up of context, process, organization, task, and actor is used as a theoretical lens to identify and construct knowledge maps describing the integration in BbCNs. The study conducts a comprehensive review upon a bibliometric analysis based on 1019 researches into BIM and a qualitative analysis of 42 carefully selected researches into integration in BbCNs. The findings confirm that the solutions provided by these researches to support integration in BbCNs are altogether technology oriented. The sociotechnical dimensions including context, organization, task, and actor show limitations. More importantly, the major academic contributions of the study lie in offering an objective and systematic analysis of previous researches, revealing the gaps on integration in BbCNs, and advising researchers in future studies regarding the integration pentagon as an all-inclusive analysis tool. These results highlight the status quo of BbCNs knowledge and serve as a dynamic platform to allow other scholars to perform further developments of integration in BbCNs.